Parent, child, and sociocultural influences on Malaysian parenting behaviours - Zulkefly, Nor Sheereen; Dzeidee Schaff, Anis Raihan (Universiti Malaysia Sabah, 2024)
Belsky’s parenting model postulates that various factors from the parent, the child, and the sociocultural context shape parenting behaviour. Research involving parenting behaviours of adolescents within the Malaysian context is still limited especially when past literature has established the effectiveness of culturally conformed parenting. Further insights regarding factors influencing Malaysian parenting behaviours could assist in the development of prevention and intervention programs and policies to support parents in their parenting journey. This study examined the factors associated with the different types of Malaysian parenting behaviours. Parents of adolescents (N = 478) from across Malaysia participated in this cross-sectional study by responding to an online survey. Parents provided information about their sociodemographic profiles (i.e., age, gender, ethnicity, religious belief, marital status, household income), focus child profile (i.e., age, gender), mental health, parenting self-efficacy, adolescent emotional and behavioural problems (EBP) and competence, and parenting behaviours (i.e., warmth, monitoring, harsh discipline, and indigenous). Descriptive and correlation analyses were performed to determine the descriptive statistics and relationship between variables. Structural equation modelling (SEM) was utilized to investigate three key models of parenting determinants: the Parent Model, the Child Model, and the Sociocultural Model. Key findings based on the respective models highlight: 1) positive parental mental health and self-efficacy predict positive parenting behaviours, parents’ harsh discipline decreases as parents age, and mothers monitor their adolescents more as compared to fathers; 2) higher adolescent competence influences parents to practice more positive parenting behaviours, and EBP is linear to harsh discipline; and 3) ethnicity and religious beliefs have influence on parents’ warmth, monitoring, and harsh discipline behaviours. Recognizing these parenting determinants allows Malaysian-centric customization of policies and interventions that can empower parents of adolescents to develop effective parenting skills.